Role of polyvinyl alcohol in cryoprotective media: evaluating efficiency and limitations in erythrocyte freezing - Osetsky, Oleksandr; Pakhomova, Yuliia; Chekanova, Valentyna; Hvozdiuk, Yana (Problems of Cryobiology and Cryomedicine, 2025)
The paper substantiates the feasibility and determines the peculiarities of using polyvinyl alcohol in multicomponent media based on penetrating cryoprotectants during rapid cooling of human erythrocytes. Polyvinyl alcohol is recommended to be used only as a part of multicomponent media based on penetrating cryoprotectants with a low glass transition temperature Tg = –100 ... –150 °C (glycerol, 1,2-propanediol). A cryoprotective effect of combined media containing polyvinyl alcohol of different molecular weights in combination with 20 % glycerol or 1,2-propanediol during freezing of human erythrocytes was comparatively assessed. Based on the results of erythrocyte preservation, the solution containing 20 % glycerol and 0.5 % polyvinyl alcohol with a molecular weight of 9 kDa was found to have the most optimal cryoprotective effect of all the studied combined media. Probl Cryobiol Cryomed 2025; 35(1):14–22